Dampak Live Streaming, Celebrity Endorsement, Alat Promosi, Review Online, Keamanan, Kemudahan Penggunaan dan Kenyamanan terhadap Perilaku Belanja Pakaian Online pengguna Tiktok setelah Pandemi Covid-19 di Jakarta - Michelle Farran; Ronald Ronald; Amelia Amelia (Journal of Management and Bussines (JOMB), 2024)
This research aims to determine the significant influence of several factors on the online shopping behavior of TikTok users during the Covid-19 pandemic in Jakarta. This research used the Structural Equation Modeling Partial Least Squares (SEM-PLS) method with a total of 215 respondents. The data that has been collected is processed using the SmartPLS application, ensuring accurate statistical analysis. The research results show that all the variables studied have a significant influence on the online shopping behavior of TikTok users during the pandemic in Jakarta. Of all the factors observed, online reviews emerged as the most influential variable and played an important role in shaping users' purchasing decisions. In contrast, the variable that has the least influence is security, indicating that although important, security factors have a more limited impact in influencing TikTok users' online shopping decisions. In conclusion, this research provides important insights into the factors that influence TikTok users' online shopping behavior during the pandemic. Keywords: Celebrity Endorsement, Live Streaming, Promotional Tools